Development and Validation of a RP-UPLC Method for Determination of Linezolid in Pharmaceutical Formulation - suryawanshi, shivraj vithal; Bhusnure, Omprakash G.; Vijayendra Swamy, S.M.; Gholve, Sachin B.; Girm, Padmaja S.; Birajdar, Mahesh J. (Journal of Drug Delivery and Therapeutics, 2019)
A simple, sensitive and accurate RP-UPLC method has been developed for the determination of Linezolid in Tablet formulation. The mix of the Linezolid was found to be 251nm in Acetonitrile: Buffer [40:60(v/v)]. The method shows high sensitivity with linearity 5 to 30μg/ml (regression r2 = 0.999). This method was tested and validated for various parameters according to ICH guidelines and USP. The Detection limit and quantitation limit were found to be 50mg ml–1 and 150 mg ml–1 in Acetonitrile: Buffer [40:60(v/v)] respectively. The results demonstrated that the procedure is accurate, precise and reproducible (relative standard deviation < 2%), while being simple, cheap and less time consuming and can be suitably applied for the estimation of Linezolid in Tablet pharmaceutical formulation.Keywords: linezolid, Acetonitrile: Buffer 40:60 (v/v). RP-UPLC, Methanol.